Predictive value of skeletal muscle mass for immunotherapy with nivolumab in non‐small cell lung cancer patients: A "hypothesis‐generator" preliminary report. Issue 2 (2nd January 2019) - Cortellini, Alessio; Verna, Lucilla; Porzio, Giampiero; Bozzetti, Federico; Palumbo, Pierpaolo; Masciocchi, Carlo; Cannita, Katia; Parisi, Alessandro; Brocco, Davide; Tinari, Nicola; Ficorella, Corrado
Abstract : Sarcopenia represents one of the hallmarks of all chronic disease, including non‐small cell lung cancer (NSCLC). A computed tomography scan is an easy modality to estimate the skeletal muscle mass through cross‐sectional image analysis at the level of the third lumbar vertebra (L3). Baseline skeletal muscle mass (SMM) was evaluated using gender‐specific cutoffs for skeletal muscle index in NSCLC patients administered immunotherapy with nivolumab to evaluate its possible correlations with clinical outcomes. From April 2015 to August 2018, 23 stage IV NSCLC patients were eligible for image analysis. Nine patients (39.1%) had low SMM. Among patients with baseline low and non‐low SMM, median progression free survival was 3.1 and 3.8 months, respectively ( P = 0.0560), while median overall survival was 4.1 and 13 months, respectively ( P = 0.2866). This hypothesis‐generating preliminary report offers the opportunity to speculate about the negative influence of sarcopenia on immune response. In our opinion, nutritional status could affect the clinical outcomes of immunotherapy, even if we cannot make definitive conclusions here. Further studies on the topic are required.